ESTIMATING THE EFFECT OF THE COVID-19 OUTBREAK EVENTS ON THE INDONESIA SECTORAL STOCK RETURN - Salsa Dilla; Linda Karlina Sari; Noer Azam Achsani (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
COVID-19 has become a global issue that bought a simultaneous effect all over the world. This outbreak has caused a significant impact on the economic stability including the stock market performance. This research used event study methodology to evaluate the Indonesia’s sectoral stock market performance which is represented by companies with the biggest market capitalization in Indonesia. Estimating the COVID-19 outbreak events, the sample of the study consisted of daily sectoral indices stock data from 1 December 2017 to 14 April 2020. The market model is used to predict expected stock returns and simple regression to get the parameters of the equation. By using a t-test, it can be concluded whether the virus outbreak caused an abnormal return on the sectoral indices. The finding showed that the abnormal returns were found in the Basic Industry and Chemicals sector, Infrastructure, Utilities and Transportation sector, Agricultural sector and Mining sector. Furthermore, Basic Industry and Chemical sector, which is represented by Barito Pasific Ltd., give the greatest reaction to the stock market performance in Indonesia due to COVID-19. Keywords: abnormal return, event study, stock return, COVID-19, Indonesia